Active Mechanical Threading by a Molecular Motor - Bach, Nicolai; Josef, Verena; Maid, Harald; Dube, Henry (Angewandte Chemie International Edition, 2022)
Molecular motors transform external energy input into directional motions and offer exquisite precision for nano-scale manipulations. To make full use of molecular motor capacities, their directional motions need to be transmitted and used for powering downstream molecular events. Here we present a macrocyclic molecular motor structure able to perform repetitive molecular threading of a flexible tetraethylene glycol chain through the macrocycle. This mechanical threading event is actively powered by the motor and leads to a direct translation of the unidirectional motor rotation into unidirectional translation motion (chain versus ring). The mechanism of the active mechanical threading is elucidated and the actual threading step is identified as a combined helix inversion and threading event. The established molecular machine function resembles the crucial step of macroscopic weaving or sewing processes and therefore offers a first entry point to a “molecular knitting” counterpart.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Hemithioindigo; Indigoids; Molecular Machines; Molecular Motors; Photochemistry